2012
DOI: 10.1080/01904167.2012.689907
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Acquisition of Organic Nitrogen in Soils Between Bok Choy and Tomato

Abstract: 2 Seedlings of bok choy and tomato were grown in soils with different nitrogen (N) sources [no N (−N), ammonium sulfate (AS), and cattle farmyard manure (CM)]. Comparison between soils treated with −N and CM indicated that the growth and N accumulation in bok choy were significantly enhanced by CM treatment, whereas no difference was found in tomato. In the rhizosphere soils, the highest protease activity was detected in CM treatment irrespective of species. Correlation analysis between rhizospheric protease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The concentrations of inorganic N and TAA were analyzed in the soil samples. The inorganic N (NH 4 + -N and NO 3 – -N) was extracted from the soil by shaking with 2 M KCl . The soil (1 g) was shaken with the 2 M KCl (5 mL) in 10 mL volume polycarbonate tubes on an end-to-end shaker (200 rpm, 30 min).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of inorganic N and TAA were analyzed in the soil samples. The inorganic N (NH 4 + -N and NO 3 – -N) was extracted from the soil by shaking with 2 M KCl . The soil (1 g) was shaken with the 2 M KCl (5 mL) in 10 mL volume polycarbonate tubes on an end-to-end shaker (200 rpm, 30 min).…”
Section: Methodsmentioning
confidence: 99%
“…It has been well documented that the responses to organic matter in terms of growth and N uptake differ among plant species. Some plants possess the ability to acquire and metabolize organic N (ON) efficiently in the form of amino acids, , peptides, , and proteins . Once applied to the soil, organic matters undergo stepwise mineralization, including proteolysis, ammonification, and nitrification, where proteinaceous compounds are converted into amino acids, ammonium (NH 4 + ), and nitrate (NO 3 – ) by soil bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Significant negative correlations between the phosphate buffer-extractable soil organic N and soil protease activity in near-rhizosphere soil with CM treatment also support this hypothesis (Figure 8). Different growth responses to mixed cropping with lupin between timothy and orchard grass may be due to different uptake characteristics of low-molecular-weight peptides and amino acids between these two grass species (Pirhofer-Walzl et al 2012;Watanabe et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…with NPI. Brassica chinensis is popular as a leafy vegetable because of its ease of growth in a variety of climatic and soil conditions, 16,17 production and storage, and high nutritional value from folate and vitamins; China is one of the largest producers of B. chinensis L . 18 …”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that NPI can improve the yield, quality and WUE of a variety of crops (tomatoes, peppers, cabbage, tobacco, cucumber and crown daisy), 1,4,6,15 but little has been reported on regarding the production of B. chinensis L. with NPI. Brassica chinensis is popular as a leafy vegetable because of its ease of growth in a variety of climatic and soil conditions, 16,17 production and storage, and high nutritional value from folate and vitamins; China is one of the largest producers of B. chinensis L.. 18 Brassica chinensis L. is a common greenhouse horticultural crop but little is known regarding how micro-irrigation versus conventional irrigation affects production. It is important to find the appropriate water and fertilizer parameters for actual agricultural production using NPI.…”
Section: Introductionmentioning
confidence: 99%